Multispecies transcriptomes reveal core fruit development genes - Rajewski, Alex; Maheepala, Dinusha C.; Le, Jessica; Litt, Amy (Frontiers in Plant Science, 2022)
During angiosperm evolution there have been repeated transitions from an ancestral dry fruit to a derived fleshy fruit, often with dramatic ecological and economic consequences. Following the transition to fleshy fruits, domestication may also dramatically alter the fruit phenotype via artificial selection. Although the morphologies of these fruits are well documented, relatively less is known about the molecular basis of these developmental and evolutionary shifts. We generated RNA-seq libraries from pericarp tissue of desert tobacco and both cultivated and wild tomato species at common developmental time points and combined this with corresponding, publicly available data from arabidopsis and melon. With this broadly sampled dataset consisting of dry/fleshy fruits and wild/domesticated species, we applied novel bioinformatic methods to investigate conserved and divergent patterns of gene expression during fruit development and evolution. A small set of 121 orthologous “core” fruit development genes show a common pattern of expression across all five species. These include key players in developmental patterning such as orthologs of KNOLLE, PERIANTHIA, and ARGONAUTE7. GO term enrichment suggests that these genes function in basic cell division processes, cell wall biosynthesis, and developmental patterning. We furthermore uncovered a number of “accessory” genes with conserved expression patterns within but not among fruit types, and whose functional enrichment highlights the conspicuous differences between these phenotypic classes. We observe striking conservation of gene expression patterns despite large evolutionary distances, and dramatic phenotypic shifts, suggesting a conserved function for a small subset of core fruit development genes.